(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
The article is an exegesis of the discursive apotheosis of motherhood/ mothering in Highway Queen (2011). It particularly analyses the narrative’s manipulation of motherhood as a vital and strategic life-support resource in a context that, in some scholarly circles, has come to be known as the ‘decade of crisis’ in Zimbabwe. That the mother character is identified with both the search for and the application of, in a pragmatic manner, life-giving values, fi rmly locates her as the “center of life, the magnet that holds the social cosmos intact and alive” (Sofola as cited in Hudson-Weems, 1993, p. xviii). This construction of motherhood resonates with the place, status and role of the African mother in antiquity where she has always been an important part of the equation of life. Remarkably, Highway Queen accomplishes an ingenious role-reversal within Zimbabwe’s literary landscape where male characters have been depicted as exclusive avatars of agency in more tempestuous and tranquil situations alike, while women are forced to contend with the victim tag in either context. Highway Queen propagates a topsy-turvy world in which the woman is invested with more agency in a situation that threatens both genders and would normally be for the man to conquer.